Scapular dislocation in a dog - TSELEPIDIS (Σ. Θ. ΤΣΕΛΕΠΙΔΗΣ) S. T.; DESIRIS, A (Journal of the Hellenic Veterinary Medical Society, 2018)
A case of traumatic scapular dislocation is described in a dog. The etiology, clinical signs, radiological findings and main complications of this uncommonly met condition are described. The surgical approach, the reduction of the dislocated scapula in its normal position and the scapular support by wiring around the 2nd rib are described and discussed. Postoperatively a Velpeau sling is applied for 2-3 weeks followed by physical therapy of the affected limb for another period of 2 weeks time.